The effect of wood composition and compatibilisers on polyethylene/wood fibre composites - Shebani, Anour N. (Stellenbosch : University of Stellenbosch, 2010)
Thesis (PhD (Chemistry and Polymer Science))--University of Stellenbosch, 2010.